Біоморфологічна структура флори Східного Полісся у контексті созологічної цінності - Lukash, O.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2009)
The biomorphological analysis of flora East Polissia is carried out. The laws of distribution of the vital forms in cenofloras depending on conditions of environment and sozology value of vital forms was established.